Management competencies for preventing and reducing stress at work : identifying and developing the management behaviours necessary to implement the HSE management standards - Yarker, Joanna; Lewis, Rachel; Donaldson-Feilder, Emma; Flaxman, Paul (Sudbury, 2007)
"This report presents the findings of the first phase of a research project which aimed to identify the specific management behaviours associated with the effective management of stress at work and to build a management competency framework for preventing and reducing stress at work. The project also aimed to identify those behaviours associated with each of the six HSE Management Standards and those behaviours associated with the implementation of the Standards. A final aim was to explore the possible integration of the emergent competency framework into existing management competency frameworks.